A Petri net based simulation to study the impact of customer response to stock-out on supply chain performance - Xiaoling Zhang (Cogent Engineering, 2016)
Based on a Petri-net based simulation model, we investigate the effect of different customer response to stock-out on both the stock-out supply chain and the competing supply chain. Five types of customer stock-out responses are incorporated in the model to quantitatively assess the correlation between customer response and supply chain performance including bullwhip effect (BWE), on-hand inventory, and backlog level. After presenting the results of a series of Petri-net based simulation experiments, we discuss opportunities for both manufacturers and retailers to work better together to mitigate supply chain disruption. We also discuss the value of information sharing on mitigating BWE.